(untitled) (Labor and Human Development Law Journal, 2018)
The historical process of maturation of the treatment for Occupational Safety and Health (OSH) demonstrates, at least in the conceptual scope, an evolution towards the empowerment of the worker. In Brazil, “Worker’s Health” (WH) has emerged as a criticism of the ‘single cause’ view between disease and specific agent currently held in the field of Occupational Health and Occupational Medicine, and has placed health as a fundamental right and sickness at work as a complex issue. In this new institutional and normative structure, workers became bearers of knowledge emanating from their experience and essential agents of transformative actions. However, there are several challenges for implementing such promises, such as: the legislation delegates to private management core issues of WH protection and of accident prevention; the dispersion of responsibility for the protection of OSH by an excessive number of state organs and the lack of unity in their actions; the creation of applications and websites to facilitate and encourage the workers themselves to exploit rights to insecure work environments is welcome but insufficient because it will make little difference if there is no fiscal structure to handle demand. The improvement of social control must include the intensification of the leading role of unions and the coordinated and collaborative action of the state organs responsible for OSH protection. It is therefore urgent to think of ways for the active participation of workers in OSH, the action on the determinants of accidents and the prioritization of preventive measures to become part of the reality of WH in Brazil. KEYWORDS: Worker’s health. Occupational safety and health. Public health. Legislation. Public Policy.